Vortex project file for PVA of Southern Resident Killer Whale -- manuscript by Williams et al. ... - Lacy, Robert C; Williams, Rob (Zenodo, 2023)
Project file for Vortex PVA scenarios used in Williams et al. manuscript. Williams, R., R.C. Lacy, E. Ashe, L. Barrett-Lenard, T.M. Brown, J.K. Gaydos, F. Gulland, M. MacDuffee, B.W. Nelson, K.A. Nielsen, H. Nollens, S. Raferty, S. Reiss, P.S. Ross, M.S. Collins, R. Stimmelmayr, & P. Paquet. 2024. Warning sign of an accelerating decline in critically endangered killer whales (Orcinus orca). Communications Earth & Environment (in press). ...